Urban environment as an independent predictor of insulin resistance in a South Asian population. - Thanikachalam, Mohan.; Fuller, Christina H.; Lane, Kevin J. (Tufts University. Tisch Library., 2019)
Background: Developing countries, such as India, are experiencing rapid urbanization, which may have a major impact on the environment: including worsening air and water quality, noise and the problems of waste disposal. We used health data from an ongoing cohort study based in southern India to examine the relationship between the urban environment and homeostasis model assessment of insulin resistance (HOMA-IR).; Keywords: Urban, Insulin resistance, Diabetes, India, HOMA-IR.; Springer Open.